2021
DOI: 10.1097/j.pain.0000000000002196
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the ICD-11 chronic pain classification with ICD-10: how can the new coding system make chronic pain visible? A study in a tertiary care pain clinic setting

Abstract: Pain is a frequent reason for patients to ask for medical services. However, systematic information about the extent and impact of pain, especially in developing countries, has not been available up to now. We evaluated whether the 11th edition of the International Statistical Classification of Diseases and Related Health Problems (ICD) can fill this gap by coding all electronic out-patient medical records of the pain clinic at Siriraj Hospital in Thailand in 2019 (8714 visits), using the ICD-10 and ICD-11 bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
1
20
0
4
Order By: Relevance
“…El trastorno musculoesquelético más frecuente ha sido la lumbalgia, seguido de la cervicalgia y, finalmente, el síndrome de hombro doloroso; mucho menos frecuentes han sido los informes de solicitud de fisioterapia por secuelas de fracturas y por epicondilitis. La lumbalgia, reconocida en la clasificación internacional de enfermedades, actualmente en su décimo primera edición (CIE-11) (23) , comprende una multitud de enfermedades como posibles causas de este síntoma; la columna lumbar, al ser uno de los ejes de sostén y estabilidad más importantes del cuerpo, es proclive a lesiones ergonómicas ocupacionales y a lesiones traumáticas (24) , debido a ello, es la principal causa de dolor musculoesquelético en más de 160 naciones, y diversos artículos de diferentes países y realizados en diferentes grupos poblacionales coinciden en ello (25) .…”
Section: Discussionunclassified
“…El trastorno musculoesquelético más frecuente ha sido la lumbalgia, seguido de la cervicalgia y, finalmente, el síndrome de hombro doloroso; mucho menos frecuentes han sido los informes de solicitud de fisioterapia por secuelas de fracturas y por epicondilitis. La lumbalgia, reconocida en la clasificación internacional de enfermedades, actualmente en su décimo primera edición (CIE-11) (23) , comprende una multitud de enfermedades como posibles causas de este síntoma; la columna lumbar, al ser uno de los ejes de sostén y estabilidad más importantes del cuerpo, es proclive a lesiones ergonómicas ocupacionales y a lesiones traumáticas (24) , debido a ello, es la principal causa de dolor musculoesquelético en más de 160 naciones, y diversos artículos de diferentes países y realizados en diferentes grupos poblacionales coinciden en ello (25) .…”
Section: Discussionunclassified
“…First studies revealed that the ICD-11 chronic pain diagnoses are more accurate, less ambiguous, and easier to use than the chronic pain diagnoses available in the ICD-10 , 1 and that the amount of residual diagnoses (eg, “chronic pain, unspecified”) is considerably smaller when using the ICD-11 compared with the ICD-10 . 49…”
Section: Discussionmentioning
confidence: 99%
“…First studies revealed that the ICD-11 chronic pain diagnoses are more accurate, less ambiguous, and easier to use than the chronic pain diagnoses available in the ICD-10, 1 and that the amount of residual diagnoses (eg, "chronic pain, unspecified") is considerably smaller when using the ICD-11 compared with the ICD-10. 49 Some limitations need to be considered when interpreting the results. Although the results provide strong initial evidence of global applicability of the classification system in specialty pain clinic settings, generalizing them to all countries and settings would be rash.…”
Section: Discussionmentioning
confidence: 99%
“…First field studies show that the classification fulfils the formal criteria required for its smooth use, 3,4 for its reliability and global applicability, 36 and improves the visibility of CP. 78 The clinicians who participated in these studies rated the clinical utility of the diagnoses as very high, indicating that they considered the classification as a tool that will help to improve the communication of pain diagnoses to patients and other colleagues, to unify language (eg, regarding clinical documentation and data collection), and to facilitate treatment selection as well as pain management. 36 To reap the benefits of this achievement, the classification should be used and implemented globally-this will be the next task the pain community faces.…”
Section: Discussionmentioning
confidence: 99%